2006
DOI: 10.1103/physrevb.73.085201
|View full text |Cite
|
Sign up to set email alerts
|

Antibonding configurations of hydrogen in silicon-germanium alloys

Abstract: Defects with a hydrogen atom at an antibonding site are identified in germanium-rich SiGe alloys ͑Ge 1−x Si x ͒ implanted with protons at low temperatures. Infrared absorption spectra of proton-implanted Ge 1−x Si x reveal hydrogen-related absorption lines, which are similar to those observed previously in pure germanium, together with three unreported absorption lines. For crystals with a silicon content of 1.2 at. % these three lines are observed at 815.8, 1430.2, and 1630.7 cm −1 . The three lines are ascri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
4
8
0
Order By: Relevance
“…We use the notation H 2 ** following the authors in Ref. [16], who associated several peaks in their Fourier Transform Infrared Spectroscopy (FTIR) spectrum to that dimer. In the literature, the same notation has been used to label a different H complex [14].…”
Section: A Bond Centered Hydrogen (Bch)mentioning
confidence: 99%
See 4 more Smart Citations
“…We use the notation H 2 ** following the authors in Ref. [16], who associated several peaks in their Fourier Transform Infrared Spectroscopy (FTIR) spectrum to that dimer. In the literature, the same notation has been used to label a different H complex [14].…”
Section: A Bond Centered Hydrogen (Bch)mentioning
confidence: 99%
“…There is strong experimental evidence of the dissociation of the BCH complex into both these complexes. In n-type Si crystals, with proton implanted below 40 K, three new peaks in the FTIR absorption spectrum were observed that became stronger upon heat treatment at temperatures in the range 50 -300 K [16]. After annealing at 320 K the three peaks disappeared.…”
Section: A Bond Centered Hydrogen (Bch)mentioning
confidence: 99%
See 3 more Smart Citations